2020
DOI: 10.3168/jds.2019-16974
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping more cows increases genetic gain and reduces rate of true inbreeding in a dairy cattle breeding scheme using female reproductive technologies

Abstract: Both small dairy cattle populations and dairy cattle populations with a low level of linkage disequilibrium (LD) suffer from low reliability of genomic prediction. In this study, we investigated whether adding more genotyped cows to the reference population influences the rate of genetic gain and rate of inbreeding by affecting the reliability. A standard breeding program with a large reference population and high LD, which mimicked a breeding program for Danish Holstein population, was simulated as a referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…A larger investment into genotyping also increased update and size of the training population, which assisted in achieving genetic gain. This is in agreement with Thomasen et al [21] who showed that adding more cows yearly to the training population increases genetic gain.…”
Section: Increasing the Investment Into Genotypingsupporting
confidence: 92%
“…A larger investment into genotyping also increased update and size of the training population, which assisted in achieving genetic gain. This is in agreement with Thomasen et al [21] who showed that adding more cows yearly to the training population increases genetic gain.…”
Section: Increasing the Investment Into Genotypingsupporting
confidence: 92%
“…The founder population was simulated for 3,000 discrete generations, and the numbers of both sexes always remained the same, and it was always random mating with replacement between males and females. The detailed simulation set-up for founder population applied in this study was same as the "diverse" breeding program tailed for Red dairy cattle in Thomasen et al (2020), which intensively elaborates information such as the number and the length of chromosomes, the initial numbers and distribution of QTL and SNP markers, set-up regarding expansion and bottleneck of the population size, the rule of descendants inheriting alleles, the selection of the final QTL and SNP markers, and so on. At generation t = −1, 2,000 QTL and 40,000 SNP loci were obtained; chromosomes from 300 male and 300 female founders were gathered by sex to form 30 paternal and 30 maternal pools each with 600 chromosomes.…”
Section: Simulation Proceduresmentioning
confidence: 99%
“…Genomic selection breeding programs realize larger improvement in genetic gain by cooperation than PS breeding programs (Täubert et al, 2011;Thomasen et al, 2020) because of increased selection intensity and accuracy. The increased selection intensity due to incorporating external animals as candidates (Banos and Smith, 1991;Smith and Banos, 1991;Mulder and Bijma, 2006) also applies to PS breeding programs.…”
Section: Improvements In Genetic Gain and Rate Of Inbreedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic diversity in French dairy cattle breeds is typically monitored using pedigree-based inbreeding estimates ( VARiabilité génétique des RUMinants et des Equidés , genetic variability in ruminants and equines, VARUME) [ 13 ]. However, more accurate and comprehensive evaluations can be obtained using genomic data [ 6 , 14 , 15 ]. In particular, inbreeding estimates based on genotypes and runs of homozygosity (ROH), in particular, have been shown to be as efficient, if not more, in evaluating and managing genetic diversity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%